Decentralized clinical trials are better for the participants and for the planet: the case study of a double-blind randomized controlled trial in Singapore (PROMOTE study) - Lisa R. Fries; Nadia Khaled; Ivan Viveros Santos; Elvira Suniega-Tolentino; Motshewa Sesing; Melissa P. S. Toh; Chui Yuen Yang; Shiao Yng Chan; Shiao Yng Chan; Sara Colombo Mottaz (Frontiers in Public Health)
IntroductionNovel technologies have enabled the decentralization of many aspects of clinical trials, but little research has been done on the impact of these changes on the participant experience, trial operations, or the environment.MethodsA fully decentralized clinical trial conducted in Singapore is used as a case study to evaluate the operational outcomes, environmental impact (via life cycle assessment), and participants experience (qualitative interviews) of the decentralized model compared to a traditional study with in-person visits.ResultsThe decentralized study achieved high participant retention rates (97%) and high completion rates for clinical data, even for biological samples. Participants found the decentralized model to be convenient and safe, especially during the pandemic. Moreover, the decentralized model was found to be more environmentally friendly and less detrimental to human health compared to traditional face-to-face clinical trials, primarily by reducing participants’ use of cars for site visits.DiscussionWhile this study focused on the environmental impact, it is important to consider other factors such as participant safety, convenience, and data quality when evaluating the suitability of a decentralized clinical trial approach. Careful planning of data flow, database structure, and data protection measures is essential. This study contributes to improving the environmental footprint of clinical trials. Environmental sustainability should be among the factors that are evaluated when selecting trial models. Decentralized and hybrid clinical trials offer efficiency, effectiveness, and environmental benefits. Further research and adoption of these approaches are encouraged.